Analisis Metode Economic Order Quantity (EOQ) Pada Manajemen Persediaan Barang Dagang Di Toko Cosplay Deimaru - Budi, Ricky Setya; Giningroem, Dewi Sri Woelandari Pantjolo; Navanti, Dovina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Without proper inventory management, the risk of excess or shortage of stock can disrupt business performance and incur additional costs. Therefore, an effective inventory management strategy is needed to meet customer demand while maintaining profitability. The objectives of this study are, first, to analyze the current inventory management at Toko Cosplay DeiMaru. Second, to analyze the application of the EOQ method in determining the optimal order quantity at Toko Cosplay DeiMaru. Third, to evaluate the effectiveness of the EOQ method in optimizing inventory costs at Cosplay DeiMaru Store. The method used is a descriptive quantitative method. The results of this study indicate that the application of the EOQ method yields effective results in optimizing order quantities, reducing inventory costs, and improving inventory management efficiency at Cosplay DeiMaru Store.